OPTIMIZATION OF CULTURAL PARAMETERS FOR THE PRODUCTION OF ANTIMICROBIAL COMPOUND FROM ENTEROCOCCUS FAECIUM CST-1 (MCC-2729) - Lalam, Chandra Mouli; Srinivasan, T.; Talluri, Vssl Prasad; Y., Naidu P. (International Journal of Current Pharmaceutical Research, 2015)
Objective: To improve the productivity of antibacterial compounds of Eenterococcus feacium CST-1 by optimizing its nutrient and physical factors and screened for its antimicrobial activity by agar well diffusion method. Methods: In order to improve its efficiency, the effects of medium components carbon and nitrogen sources, temperature, pH, agitation, incubation time, were optimized and its productivity was determined by agar well diffusion method against four bacterial strains obtained from MTCC, Chandigarh, India namely Bacillus subtilis, E. coli, Psudomonas aeruginosa, Staphylococcus aureus,. Results: The bacterial inhibition rate was more in the optimized medium composition (g/100 ml), containing tryptone 1.5, dextrose 3.0 and incubation time for 76 hrs, temperature 35Â±2 Â°C and pH 6.5. Compared to basal medium the optimized medium shown about 1.2 fold increased in the zone of inhibition by Enterococcus feacium CST-1. Conclusion: The results from this study confirmed that the antibacterial substances produced by Eenterococcus feacium CST-1 were found to be more effective after its optimization.